Myeloma is characterized by stage specific alterations in DNA methylation that occur early during myelomagenesis - Heuck, Christoph J. (J Immunol, 2013)
Epigenetic changes play important roles in carcinogenesis and influence initial steps in neoplastic transformation by altering genome stability and regulating gene expression. To characterize epigenomic changes during the transformation of normal plasma cells to myeloma, we modified the HELP assay to work with small numbers of purified primary marrow plasma cells. The nano-HELP assay was used to analyze the methylome of CD138+ cells from 56 subjects representing premalignant (MGUS), early and advanced stages of myeloma as well as healthy controls. Plasma cells from premalignant and early stages of myeloma were characterized by striking, widespread hypomethylation. Gene specific hypermethylation was seen to occur in the advanced stages and cell lines representative of relapsed cases were found to be sensitive to decitabine. Aberrant demethylation in MGUS occurred primarily in CpG islands while differentially methylated loci in cases of myeloma occured predominantly outside of CpG islands and affected distinct sets of gene pathways, demonstrating qualitative epigenetic differences between premalignant and malignant stages. Examination of the methylation machinery revealed that the methyltransferase, DNMT3A, was aberrantly hypermethylated and underexpressed, but not mutated in myeloma. DNMT3A underexpression was also associated with adverse overall survival in a large cohort of patients, providing insights into genesis of hypomethylation in myeloma. These results demonstrate widespread, stage specific epigenetic changes during myelomagenesis and suggest that early demethylation can be a potential contributor to genome instability seen in myeloma. We also identify DNMT3A expression as a novel prognostic biomarker and suggest that relapsed cases can be therapeutically targeted by hypomethylating agents.